Issues regarding ethics among tertiary students / Aishah Musa...[et al.] - Musa, Aishah; Ismail, Junaida; Ladisma @ Awis, Ladisma @ Awis (2019)
Issues regarding ethics are common among tertiary students. Ethics is defined as "the study of moral principles or values that determine whether actions are right or wrong and outcomes are good or bad" (McShane & Glinow, 2008). This study seeks to find out on the issue of ethics among tertiary students. In general, the purpose of this study is to investigate the ethical behaviours among the students in UiTM Kedah. This study will focus on four factors of academic environment namely; violation of school / university regulations, academic cheating, computer ethics and selfishness.